Profil uretritis gonokokus dan uretritis non gonokokus di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari – Desember 2013 - Palenewen, Jonna; Mawu, Ferra O.; Niode, Nurdjanah J. (Universitas Sam Ratulangi, 2016)
Abstract: Gonococcal urethritis (GU) is an inflammation of the urethra caused by Gram negative bacteria Neisseria gonorrhoeae associated with complaints of itching and burning sensation, pain during urination, mucopurulent urethral discharge from the tip of the urethra which sometimes bleeds, and pollakiuria. Non-gonococcal urethritis (NGU) is an inflammation of the urethra caused by Gram-negative bacterium Chlamydia trachomatis which is transmitted through sexual contact. Symptoms include mild dysuria, an uneasy feeling in the urethra, pollakiuria, and seropurulent urethral discharge. This study aimed to determine the profile of gonococcal urethritis and non-gonococcal urethritis in the Dermatovenereology Clinic of Prof. Dr. R. D. Kandou Hospital Manado from January-December 2013. This was a retrospective descriptive study based on the type of disease (GU or NGU), age, occupation, and sexual orientation. The results showed 204 cases of sexual transmitted infections (STIs). There were 27 cases of GU (6 %) and 10 cases of NGU (2 %). Most of GU and NGU patients were 25-44 years (17,46%) with private employment (17,47 %), and sexual orientation to heterosexual (37,10 %). Keywords: gonococcal urethritis, non-gonococcal urethritisAbstrak: Uretritis gonokokus (UG) ialah peradangan uretra disebabkan oleh bakteri Gram negatif Neisseria gonorrhoeae dengan keluhan gatal, panas, nyeri saat berkemih, dapat disertai keluar duh tubuh mukopurulen dari ujung uretra yang kadang mengeluarkan darah, dan polakisuria. Uretritis non gonokokus (UNG) ialah peradangan uretra disebabkan oleh bakteri Gram negatif Chlamydia trachomatis yang ditularkan melalui kontak seksual. Gejala berupa disuria ringan, perasaan tidak enak di uretra, polakisuria, dan keluarnya duh tubuh seropurulen. Penelitian ini bertujuan untuk mengetahui profil uretritis gonokokus dan non gonokokus di Poliklinik Kulit dan Kelamin RSUP Prof Dr. R. D. Kandou Manado periode Januari-Desember 2013. Jenis penelitian ini deskriptif retrospektif berdasarkan jenis penyakit (UG atau UNG), usia, pekerjaan, dan orientasi seksual. Hasil penelitian menunjukkan dari 204 kasus infeksi menular seksual (IMS) terdapat 27 kasus UG (6%) dan 10 kasus UNG (2%). Penderita terbanyak pada kelompok usia 25-44 tahun (17,46%), dengan pekerjaan swasta (17,47%), serta orientasi seksual dengan heteroseksual (37,100%).Kata kunci: uteritis gonokokus, uretritis non gonokokus